Perylene‐Based Bis‐, Tetrakis‐, and Hexakis(terpyridine) Ligands and Their Ruthenium(II)–Bis(terpyridine) Complexes: Synthesis and Photophysical Properties. Issue 18 (5th May 2013) - El‐Batal, Hany; Guo, Kai; Li, Xiaopeng; Wesdemiotis, Chrys; Moorefield, Charles N.; Newkome, George R.
Abstract: A series of metallodendrimers9 –11, as well as their corresponding ligands, were designed and synthesized. These materials integrate perylene as a functional core with termini; both chromophores are known for their photovoltaic properties. The products were fully characterized by a combination of 1 H NMR and 13 C NMR spectroscopy, COSY, and MS. Their photophysical properties revealed a broad absorption spectrum with enhanced molar absorption coefficients corresponding to the increase in the number of units, which is indicative of their potential as candidates for light harvesting. Abstract : A family of functional materials bearing a perylene core and terpyridine branches, along with their Ru II –bis(terpyridine) complexes, was designed and synthesized. Their structures were elucidated by NMR spectroscopy and MS. Their optical properties showed absorption spectra that ranged from 250 to 625 nm, which suggests their possible use as sensitizers for dye‐sensitized solar cells.